A needs-assessment survey of the high school LGBTQ+ environment by a health science center interprofessional team - Velasquez, Rafael; Moore, Mary E.; Sheets, Gabrielle; Nieves-Rivera, Christian; Van Nuland, Sonya; Cuccia, Martha; Tsien, Fern; Hollenbach, Andrew D. (Frontiers in Sociology, 2024)
Despite improvements in the awareness and acceptance of lesbian, gay, bisexual, transgender, queer, and other sexual and gender diverse (LGBTQ+) individuals, the LGBTQ+ community continues to experience discrimination, which can result in adverse health outcomes. In particular, LGBTQ+ youth have an increased risk of experiencing depression, substance abuse, and suicide. Societal stigma and rejection, bullying, and familial disapproval all contribute to these health disparities. In recognition of these inequities, an interprofessional team of biomedical faculty members, staff, and trainees from the Louisiana State University Health Science Center (LSUHSC) in New Orleans developed the needs-assessment evaluation, the Gender and Sexual Minority Youth Outreach Survey (GSMYO) for high school students. Health science centers have access to resources and experienced personnel who can provide support and education to high school students, teachers, and administrative staff. However, it is important to first determine the high schools’ specific needs, attitudes towards LGBTQ+ acceptance, and their current resources. Faculty, staff, and trainees from the LSUHSC Science Youth Initiative (SYI) and the LSUHSC LGBTQ+ Organization, Tiger Pride, administered the short, anonymous survey to adolescents attending Southeast Louisiana high schools. English Language Learner (ELL) students received the survey in Spanish. Results from the GSMYO needs-assessment survey are presented. Other health science centers may adapt the presented survey to develop needs-based LGBTQ+ high school programs to address the educational and health inequities in their own communities, regardless of location or demographic region.